Chloris telanganae (Chloridoideae: Poaceae), a new species from Telangana State, India - Nagaraju, Siddabathula; Prasanna, Parigi Venkateswara; Rao, Yechuri Venkateswara; Padal, Salugu Bodayya (Phytotaxa, 2020)
Chloris telanganae (Poaceae), a new species from Telangana, India, is described and illustrated. This new species is similar to C. wightiana but differs many characters which are discussed here. An updated key for Indian Chloris is also provided for easy identification.